الإيقاع العاطفي في لاميّة الشيخ عبد الرحيم أمين الله الأدبي لشيخه محمد كمال الأدبي: دراسة تحليلية نقدية أدبية - Adekilekun, Azeez Lateef; Sulayman, ‘Abd al-Wahid Jibril (SIBAWAYH Arabic Language and Education, 2025)
الملخص:يتناول هذا البحث بالدراسة والتحليل اللغوي للامية الشيخ عبد الرحيم أمين الله الأدبي (الواعظ العالمي) التي رثى بها أستاذه الشيخ محمد كمال الدين الأدبي، أحد أبرز أعالم العلم والدعوة في نيجيريا. يهدف البحث إلى الكشف عن الإيقاع العاطفي الذي يتغلغل في القصيدة، ومدى قوة شاعرية الشيخ عبد الرحيم رغم انشغاله بالدعوة أكثر من الشعر، وذلك من خلال تحليل الأسلوب، والبنية اللغوية، والموسيقي الشعرية، والصياغة التعبيرية. اعتمد الباحث المنهج الفني التحليلي القائم على تتبع القواعد األدبية واللغوية المؤثرة في البناء الجمالي للنص، مع استحضار القيم التعبيرية والنفسية بعيدًا عن ذات المنتج األدبي. ويعرّفه الباحث بأنه التأثير الانفعالي المتبادل بين المبدع والمتلقي، إذ يعبّر الأديب عن وجدانه بطريقة تجعل القارئ أو السامع يعيش الحالة العاطفية ذاتها، فيتماهى الشعور بين الطرفين.صورة موجزة عن الشيخ عبد الرحيم: يتصف الشيخ بالذكاء، وغزارة العلم، وسعة الثقافة، وحسن الخلق، والتفاني في الدعوة إلى الله داخل نيجيريا وخارجها. حاز محبة الناس وهيبتهم ببالغته ورجاحة فكره، وأسهم في تربية جيل من العلماء والدعاة، وله نتاج أدبي بارز على الرغم من انشغاله بالدعوة. تضم القصيدة أكثر من ثمانين بيتًا، افتتحها الشاعر بحمد الله والثناء على رسوله، ثم انطلق في رثاء شيخه وبيان فضله العلمي والدعوي، وفضائله الخُلُقية، وتأثيره الواسع في الناس. عكست القصيدة حزنًا عميقًا ووفاء ً نادرًا، واستحضرت صورًا مؤثرة تعبّر عن الفقيد والفناء وخلود الأثر.أظهر الشاعر تمكنًا لغويًا واضحًا في بناء التراكيب ومراعاة القواعد النحوية والصرفية، مع بعض الضرورات الشعرية المقبولة. كما تناول الباحث مواضع الحرف اللغوي الطفيف من مثل: قطع همزة الوصل في "باسم"، استعمال "كاد قد فات خيرنا" بدال ً من "كاد يذهب خيرنا"، تسكين ما وجب تنوينه، ونحو ذلك. وأشاد الباحث بقدرة الشاعر على التوازن بين اللغة الفصيحة والعاطفة الصادقة. الجانب الموسيقي: نُظمت القصيدة على بحر الطويل (فعولن مفاعيلن فعولن مفاعلن)، وهو أنسب البحور لموضوع الرثاء لما فيه من امتداد وانسياب يعبّران عن طول الألم واستمرار الحزن. حافظ الشاعر على الوزن العام مع ورود بعض الزحافات المقبولة كـ"القبض" في بعض المواضع. يعتمد الإيقاع العاطفي بالنسبة إلى تأثيره في المتلقي وإيقاظه للمشاعر على صدقية العاطفة وحرارتها وقوتها، واستمرارها من مطلع القصيدة إلى مقطعها من الجانب الواقعي والفني. تدل استمالة الشاعر أو الكاتب للقلوب عبر عمله الأدبي على معرفته لكيفية الإنشاء بنوعيه الكتابي والشغهي، وتنم عن مدى قوته في التعبير عن خلجات نفسه والتصوير لها، سواء تفرغ للإنتاج الفكري أو لم يتفرغ له. وتكسب براعة الشاعر أو الكاتب عمله إشادة المطلعين عليه بما فيه من الجودة الفنية والروعة الأدبية، بغض النظر عن منتجه،إلى جانب التطرق إلى مواطن تسترعي الانتباه إليها بالقيام بتصحيح ما تـمس به الحاجة اللغوية والبنائية، مع الاعتماد على الموضوعية لا على الذاتية، بلا مخالفة العرف السلوكي، والقيم الأخلاقية. الكلمات المفتاحية: الإيقاع، العاطفة، الدراسة، التحليل، النقد، الأدب. Abstract:This study examines and linguistically analyzes the Lāmiyyah poem by Sheikh ʿAbd al-Raḥīm Amīn Allāh al-Adabī (the international preacher), in which he elegizes his teacher, Sheikh Muḥammad Kamāl al-Dīn al-Adabī, one of the most prominent figures of knowledge and Islamic propagation in Nigeria. The study aims to uncover the emotional rhythm that permeates the poem and to demonstrate the strength of Sheikh ʿAbd al-Raḥīm’s poetic talent despite his greater preoccupation with preaching than with poetry. This is achieved through an analysis of style, linguistic structure, poetic musicality, and expressive formulation. The researcher adopts an artistic–analytical approach based on tracing the literary and linguistic principles that influence the aesthetic construction of the text, while evoking its expressive and psychological values, independent of the author’s personal identity. The researcher defines emotional rhythm as the reciprocal emotional effect between the creator and the recipient, whereby the writer expresses his inner feelings in a way that enables the reader or listener to experience the same emotional state, resulting in an emotional identification between both sides. A brief profile of Sheikh ʿAbd al-Raḥīm: he is characterized by intelligence, abundant knowledge, wide culture, noble character, and dedication to the call to God within and beyond Nigeria. He earned people’s love and respect through his eloquence and sound judgment, contributed to educating a generation of scholars and preachers, and possesses a notable literary output despite his engagement in daʿwah activities. The poem consists of more than eighty verses. It opens with praise of God and blessings upon His Messenger, then proceeds to elegize the poet’s teacher by highlighting his scholarly and missionary virtues, his moral qualities, and his broad influence among people. The poem reflects deep sorrow and rare loyalty, employing powerful imagery that evokes death, transience, and the immortality of lasting influence. The poet demonstrates clear linguistic mastery in constructing expressions and observing grammatical and morphological rules, with some acceptable poetic necessities. The researcher also addresses minor linguistic issues, such as cutting the hamzat al-waṣl in bism, using kāda qad fāta khayrunā instead of kāda yadhhabu khayrunā, the omission of required tanwīn, and similar cases. Nevertheless, the researcher praises the poet’s ability to balance classical language with sincere emotion. From the musical perspective, the poem is composed in al-Ṭawīl meter (faʿūlun mafāʿīlun faʿūlun mafāʿilun), which is considered the most suitable meter for elegy due to its length and flowing rhythm that express prolonged pain and enduring grief. The poet maintains the general meter, with some acceptable metrical variations such as al-qabḍ occurring in certain positions. Emotional rhythm, in terms of its impact on the recipient and its ability to awaken feelings, depends on the authenticity, warmth, strength, and continuity of emotion from the opening of the poem to its conclusion, both realistically and artistically. The writer’s or poet’s ability to win hearts through a literary work reflects his mastery of both written and oral expression and indicates his power to articulate and portray his inner emotions, whether or not he is fully devoted to intellectual production. Such skill earns the work critical acclaim for its artistic quality and literary beauty, regardless of the author’s broader output.The study also addresses points that merit attention through necessary linguistic and structural corrections, while adhering to objectivity rather than subjectivity and maintaining ethical and moral norms. Keywords: Rhythm, emotion, study, analysis, criticism, literature.